دور أبعاد التسويق البيئي في تعزيز سمعة المنظمة دراسة تحليلية لآراء عينة من المديرين في معامل الأسمنت في مدينة السليمانية - بايز, لاسك أرسلان; صادق, درمان سليمان (Sulaimani Journal for Humanities, 2018)
The issues of Environmental have occupied a large global attention of since the sixties of the last century from the researchers and writers and increased awareness of it in recent years among consumers and business organizations in the world generally and the developed countries in particular. In line with this development, this study deals with the role of environmental marketing dimensions in enhancing the organization reputation, therefore the importance of this research focus on the group of cement factories in the city of Sulaimani. The aim of this research was to build a philosophical intellectual base that take up the mechanism of correlation and regression between the dimensions of environmental marketing and the reputation of the organization which was built through it the research model and hypotheses. The questionnaire was designed to collect the data and distributed to the managers of cement factories in Sulaimaniyah Governorate, with (88) questionnaire. In order to analyze the data, a number of statistical methods and tools were used, including means, standard deviations, the correlation and regression analysis, simple linear regression and variance by statistical program (SPSS V.21). At the end of their analysis, the researchers reached a set of conclusions and the most important was the contribution of the dimensions of environmental marketing effectively in enhancing the reputation of the organization based on the existence of relationship and impact between them. Based on the findings of the research, the researchers presented a set of recommendations that are in line with these conclusions, the most important was the necessity of practicing the dimensions of environmental marketing in order to enhance the reputation of the organization and increase the awareness of all responsible in the all organizations concerned about the important role of environmental marketing dimensions in improving the reputation of the organizations.
Keywords: Environmental Marketing Organizations Reputation